Cytotoxic effect of Luffa cylindrica leaf extract on MCF-7 cell lines (Bangladesh Journal of Pharmacology, 2025)
This study investigated the cytotoxic effect of Luffa cylindrica leaf aqueous ethanolic extract on breast cancer cell lines MCF-7 and the normal epithelial cell line MCF-10A. Phytochemical screening and DPPH assays confirmed the presence of antioxidant compounds. MTT showed a dose-dependent reduction in cancer cell viability (p